Search for hypoglycemic agents among 1,2,4-triazole derivatives - Pruhlo, Ye. S.; Maliuhina, O. O.; Пругло, Євген Сергійович; Малюгіна, Олена Олександрівна (Warsaw : Sp. z o. o. "iScience", 2020)
Summary. This paper studied the effect of these substances, substituted 1,2,4-triazole, the level of glucose in the blood glucose tolerance test. A number of compounds with hypoglycemic action. Some regularities between chemical structure and pharmacological effect.
Keywords: 1,2,4-triazoles; hypoglycemic activity; structure-activity relationship